A Nonlinear Cutting Stock Problem - L. L. Salles Neto; A. C. Moretti (Revista Integración, 2010)
In this work we introduce a new method to minimize the number of processed objects and the setup number in a unidimensional cutting stock problem. A nonlinear integer programming problem can be used to represent the problem studied here. The term related to the minimization of the setup number is a nonlinear discontinuous function, we smooth it and generate the cutting patterns using a modified Gilmore-Gomory strategy. Numerical tests on a wide range of test problems are very encouraging and the new method compares favorably with other methods in the literature.